Assessment of pattern for consumption and awareness regarding energy drinks among medical students - Aslam, Hafiz Muhammad (BioMed Central, 2013)
BACKGROUND: Energy drink is a type of beverage which contains stimulant drugs chiefly caffeine and marketed as mental and physical stimulator. Coffee, tea, soft drinks and other caffeinated beverages are not considered as energy drinks. Purpose of our study was to evaluate the awareness of medical students regarding energy drinks and their pattern and reason of energy drinks consumption. METHODS: This was a cross sectional and observational study conducted during the period of January – December 2012 at four Medical Colleges (Dow Medical College, Sindh Medical College, Jinnah Medical College and Liaquat National Medical College) of Karachi, Pakistan. Over all 900 M.B.B.S students were invited to participate after taking written consent but viable questionnaire was submitted by 866 students, estimated response rate of 96%. All data was entered and analyzed through SPSS version 19. RESULT: Out of 866 participants, majority were females 614 (70.9%) and only 252 (28.5%) were males, with a mean age of 21.43 ± 1.51 years. Energy drinks users were 350 (42.89%) and non users were 516 (59.58%). Only 102 (29.3%) users and 159 (30.7%) non users know the correct definition of Energy drinks. Regarding awareness, mostly user and non users thought that usage of energy drinks had been on rise due to its usefulness in reducing sleep hours [users193 (43.9%), nonusers 247 (56.1%) (p < 0.05)], for studying or completing major projects [users184 (45.0%), nonusers 225 (55.0%) (p < 0.05)] and for refreshment purposes [users179 (44.9%), nonusers 220 (55.1%) (p < 0.05)]. Two main reasons of not using energy drinks by non-users were “awareness from its side effects” 247 (47.8%) and “have no specific reason” 265 (51.3%). Most common side effects reported by users were fatigue 111 (31.7%) and weight gain 102 (29.4%). CONCLUSION: In sum, the fact that despite serious side effects of weight gaining and fatigue, practice of consuming energy drinks is highly prevalent among medical students, particularly because they are ever ready to boost their energy level and reduce sleep hours due to stress of exams and projects. This warrants the creation of continued public health awareness about the appropriate use of caffeinated beverages, their potential benefits, side effects and correction of wrong perceptions.